THE USE OF ENGLISH SPELLING AND GRAMMAR CHECKER WEBSITE IN IMPROVING JUNIOR HIGH SCHOOL STUDENTS' IN WRITING NARRATIVE TEXT - Amrawati, Riski; Sulfasyah; Andi Baso, Farisha (FKIP Unismuh Makassar, 2021)
The main objective of this research was to find out the students’ difficulties in speaking at SMP PGRI Barembeng and the students’ strategies in overcoming their difficulties in writing narrative text This research used descriptive quantitative method. The participants of this research were the students’ at SMP PGRI Barembeng. The sample of this research were 44 students taken by purposive sampling technique. The researcher used the writing test as the instrument of this research. Based on the research findings, there were two students’ difficulties those were; lack of vocabulary, lack of confidence and lack of grammar. The researcher also found 23 students’ strategies in overcoming writing difficulties at SMP PGRI Barembeng, those were; memory strategy, cognitive strategy, affective strategy and social strategy.